Pengaruh Return On Assets (ROA) Dan Earning Per Share (EPS) Terhadap Harga Saham Studi Empiris Pada Perusahaan Sektor Pertambangan Sub-Sektor Batubara Periode 2021-2024 - Annisya, Laila Izza; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to find out about stocks. One of the financial instruments that is most popular with many investors is because shares have the advantage of generating higher profits when compared to other forms of investment. Mining itself is able to become the spearhead of the economy which can have an impact on annual state revenues. Keywords ; Company Share, Return On Assets (ROA), and Earning Per Share (EPS)